Does stock market development affect economic growth? Econometric evidence from Bangladesh / Abdullahil Mamun ... [et al.] - Mamun, Abdullahil; Basher, Shahanara; Hoque, Nazamul; Ali, Md Hasmat (Dr.) (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2018)
The study aims to evaluate the causality linkage between  stock market development (SMD) and growth of the economy  in Bangladesh. Using time series data of quarterly frequency through 2000Q1-2017Q4 and employing the Johansen cointegration approach the study reveals that there  are  long-run co-integrating relationships among the variables, namely, GDP, development of the stock market, net interest spread, real effective exchange rate and financial depth. The Vector Error Correction Model (VECM) confirms the presence of a long-term equilibrium relationship between GDP and other variables such as regressors as the system is found to be stable in the long-run. As revealed from the study, the short run positive impact of SMD on the growth of the Bangladesh economy sustains in the long run, which is also true for financial depth. However, financial deepening has a relatively large contribution to the output growth of Bangladesh than SMD. Granger causality tests assert that the causal association is unidirectional that runs from SMD to output growth.